2016
DOI: 10.1142/s1793545816500115
|View full text |Cite
|
Sign up to set email alerts
|

The influence on biotissue laser resection of a strongly absorbing layer at the optical fiber tip

Abstract: In this paper, we consider a method of laser resection using the silica glass core from which the cladding layer has been removed as the cutting part of a laser scalpel. An absorbing layer coating the silica¯ber tip markedly alters its biotissue cutting characteristics. The results of histological studies of skin after exposure to a laser scalpel with and without a strongly absorbing coating (SAC) at a wavelength of 0.97 m show that resection using a coated scalpel is more sparing. When an uncoated scalpel was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…13 According to a previous report, resections made using a laser scalpel with a bare tip led to the formation of a wide region (nearly 300 mm) of thermally coagulated tissue. 22 The thermal response of pancreatic cancer cells has been investigated in vitro. Exposure to 50 C for 5 minutes resulted in a significant decline in cell viability (70%) on day 1 with a continued decline to 0% by day 7 following the exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 According to a previous report, resections made using a laser scalpel with a bare tip led to the formation of a wide region (nearly 300 mm) of thermally coagulated tissue. 22 The thermal response of pancreatic cancer cells has been investigated in vitro. Exposure to 50 C for 5 minutes resulted in a significant decline in cell viability (70%) on day 1 with a continued decline to 0% by day 7 following the exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study had demonstrated the efficacy of this laser parameter for skin resection. 22 The laser light was delivered to the tissue via silica fiber 550 μm in diameter. A fiber tip cleared from the cladding layer was used for resection.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the progress in laser surgery has been mainly associated with the approbation of newly created laser sources [1][2][3] and the use of novel focusing elements [4] or coatings [5][6][7]. The effect of the laser radiation on a biological tissue has been theoretically considered in Refs [8][9][10].…”
Section: Introductionmentioning
confidence: 99%